Anaerobic and aerobic metabolism of diverse aromatic compounds by the photosynthetic bacterium Rhodopseudomonas palustris. - Harwood, C S (1988)
The purple nonsulfur photosynthetic bacterium Rhodopseudomonas palustris used diverse aromatic compounds for growth under anaerobic and aerobic conditions. Many phenolic, dihydroxylated, and methoxylated aromatic acids, as well as aromatic aldehydes and hydroaromatic acids, supported growth of strain CGA001 in both the presence and absence of oxygen. Some compounds were metabolized under only aerobic or under only anaerobic conditions. Two other strains, CGC023 and CGD052, had similar anaerobic substrate utilization patterns, but CGD052 was able to use a slightly larger number of compounds for growth. These results show that R. palustris is far more versatile in terms of aromatic degradation than had been previously demonstrated. A mutant (CGA033) blocked in aerobic aromatic metabolism remained wild type with respect to anaerobic degradative abilities, indicating that separate metabolic pathways mediate aerobic and anaerobic breakdown of diverse aromatics. Another mutant (CGA047) was unable to grow anaerobically on either benzoate or 4-hydroxybenzoate, and these compounds accumulated in growth media when cells were grown on more complex aromatic compounds. This indicates that R. palustris has two major anaerobic routes for aromatic ring fission, one that passes through benzoate and one that passes through 4-hydroxybenzoate.